On the exponential diophantine equations of degree three - Amalul Hair, Nur Hidayah; Sapar, Siti Hasana (Journal of Multidisciplinary Engineering Science and Technology (JMEST), 2019)
Diophantine equation is known as a polynomial equation with two or more unknowns which only integral solutions are sought. This paper concentrates on finding an integral solution to the exponential Diophantine equation of degree three. By looking at the pattern of the solution to the equation under consideration, we will construct theorems and lemmas. From this study, there exist two solutions to the exponential Diophantine equation of degree three that we consider.